2022
DOI: 10.3389/fmed.2022.841112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Conjunctival Sac Microbiome in Dry Eye Patients With and Without Sjögren's Syndrome

Abstract: PurposeTo analyze the conjunctival sac microbial communities in patients with Sjögren's syndrome-associated dry eyes (SSDE) and non-Sjögren's syndrome-associated dry eyes (NSSDE), compared with normal controls (NC).MethodsConjunctival sac swab samples from 23 eyes of SSDE, 36 eyes of NSSDE, and 39 eyes of NC were collected. The V3–V4 region of the 16S ribosomal RNA (rRNA) gene high-throughput sequencing was performed on an Illumina MiSeq platform and analyzed using Quantitative Insights Into Microbial Ecology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Unlike the Texas study, individuals with Sjögren’s had a significantly decreased alpha diversity compared with controls and NDE, as well as significant compositional differences (beta diversity) between the three groups. Most pronounced differences included a significantly increased relative abundance of Actinobacteria in the SDE group compared with both the NDE group and controls and a significantly decreased Cyanobacteria and Bacteroides abundance in the SDE group compared with controls 59. Similarly, in a South Korean study that examined the OSM in 48 individuals with primary Sjögren’s compared with 72 subjects with NDE, a significantly reduced alpha diversity was noted in the Sjögren’s group compared with NDE.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Unlike the Texas study, individuals with Sjögren’s had a significantly decreased alpha diversity compared with controls and NDE, as well as significant compositional differences (beta diversity) between the three groups. Most pronounced differences included a significantly increased relative abundance of Actinobacteria in the SDE group compared with both the NDE group and controls and a significantly decreased Cyanobacteria and Bacteroides abundance in the SDE group compared with controls 59. Similarly, in a South Korean study that examined the OSM in 48 individuals with primary Sjögren’s compared with 72 subjects with NDE, a significantly reduced alpha diversity was noted in the Sjögren’s group compared with NDE.…”
Section: Methodsmentioning
confidence: 92%
“…Most pronounced differences included a significantly increased relative abundance of Actinobacteria in the SDE group compared with both the NDE group and controls and a significantly decreased Cyanobacteria and Bacteroides abundance in the SDE group compared with controls. 59 Similarly, in a South Korean study that examined the OSM in 48 individuals with primary Sjögren’s compared with 72 subjects with NDE, a significantly reduced alpha diversity was noted in the Sjögren’s group compared with NDE. On the other hand, significant compositional differences were not identified between the groups.…”
Section: Methodsmentioning
confidence: 95%
“…We assumed that there were individual differences among recruited participants and further studies with large cohorts size are needed to provide more evidence of global differences of lung microbes with PCoA clustering. PLS-DA, as the supervised method, could achieve clustering for different groups but with full awareness of the group labels ( 52 54 ). Composition analysis showed that there were bacterial disturbances in some taxa, despite the most common phyla and genera reported previously ( 39 , 50 ) being the same among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…In Demodex blepharitis, the relative abundance of Proteobacteria has been shown to be higher, with lower abundances of Actinobacteria and Firmicutes in the patients with blepharitis compared to healthy controls [19]. Lower microbiome diversity was also seen in patients with non-Sjogren-associated dry eye compared to normal controls [20]. In addition, systemic diseases such as diabetes may also impact the composition of the OSM [21].…”
Section: Ocular Surface Dysbiosis and Diseasementioning
confidence: 99%